EIB Working Paper 2020/06 - Digital technologies and firm performance Evidence from Europe (Volume 2020/6) - Rückert, Désirée (European Investment Bank, 2020)
As the productivity of the European economy shows signs of slowing down, many hopes are pinned on digital technologies to reverse this trend. This study uses data from the EIBIS 2019 survey to examine whether the adoption of different digital technologies (such as advanced robotics, 3D printing, or Internet of Things) by firms in the EU have different impacts on productivity. It also examines whether these different technologies have different implications for employment growth, and whether there are complementarities between technologies when it comes to firm performance.